DEVELOPMENT OF METHODOLOGY FOR IMPLEMENTATION OF STRATEGIC PLANNING - MISP - João Alberto Neves dos Santos (Independent Journal of Management & Production, 2014)
The development of this methodology was started in 1995, aimed at the implementation of strategic planning in an organization, using principles of strategy formulation school “Design School” at Harvard University. The methodology is presented structured steps that facilitate its implementation by an organization. Has already been tested in various public organizations, but is being proposal regarding any tpe of organization. To do this, you can make use of undergraduate students to assist in investigation methods and techniques can be applied in the various stages of the methodology, could then define the most appropriate methods and techniques in each step. Noteworthy that the methodology also provides for a performance measurement system that supports the actions of strategic planning.